Assessing the Impact of a Strength-Based Parenting Program on Family Cohesion and Marital Conflicts - Mata, Giselle; Bauer, Florian; Piskorz-Ryń, Oriana (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to evaluate the effectiveness of a strength-based parenting program in enhancing family cohesion and reducing marital conflicts among parents.Methods: A randomized controlled trial design was employed with 30 participants (15 in the intervention group and 15 in the control group), all of whom were parents residing in Italy. The intervention group participated in a nine-session, strength-based parenting program delivered over nine weeks, while the control group received no intervention during the study period. Both groups completed assessments at three time points: pretest, posttest, and a five-month follow-up. The standardized tools used included the Family Adaptability and Cohesion Evaluation Scales IV (FACES IV) to measure family cohesion and the Marital Conflict Questionnaire (MCQ) to assess marital conflicts. Data were analyzed using repeated measures ANOVA and Bonferroni post-hoc tests in SPSS version 27.Findings: The repeated measures ANOVA indicated significant time × group interaction effects for both family cohesion (F(2,56) = 16.63, p < .001, η² = .39) and marital conflicts (F(2,56) = 18.38, p < .001, η² = .41). Post-hoc comparisons revealed that the intervention group experienced significant increases in family cohesion from pretest to posttest (Mean Difference = 6.87, p < .001) and follow-up (Mean Difference = 6.14, p < .001). Similarly, marital conflicts significantly decreased in the intervention group from pretest to posttest (Mean Difference = -10.85, p < .001) and remained lower at follow-up (Mean Difference = -11.19, p < .001), with no significant changes observed in the control group.Conclusion: The strength-based parenting intervention proved effective in promoting family cohesion and reducing marital conflict over time, with sustained benefits evident at a five-month follow-up. These findings highlight the value of strengths-focused approaches in enhancing family relationships and emotional well-being.